AKIBAT HUKUM PERUBAHAN REGULASI PENGADAAN BARANG DAN JASA PEMERINTAH DALAM RENOVASI BANGUNAN GEDUNG KANTOR PENGADILAN AGAMA PARIAMAN - Aprilan, Mohd. Dedy (Program Magister Ilmu Hukum Universitas Ekasakti, 2018)
The Government's renewal of Government Procurement of Goods and Servicesregulations continues to be carried out to achieve the ideal goal of GovernmentProcurement of Goods and Services, namely to ensure efficiency, transparency andfairness in the implementation of development activities by the Government. Of the manyGovernment Goods and Services Procurement work, the procurement of constructionworks is complicated by a large budget. In this work it is usually very vulnerable toirregularities and conflicts. One of the construction works is the renovation work ofGovernment office buildings.